PERAN KOMITMEN ORGANISASI DALAM MEMEDIASI KEPEMIMPINAN DAN IKLIM KERJA TERHADAP KINERJA KARYAWAN DI PT PLN NUSA DAYA UL KETAPANG - Putu Marenda Dina Ashita Putri; M. Rudi Irwansyah; Made Ary Meitriana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the effect of leadership and work climate on employee performance, with organizational commitment acting as a mediating variable. A quantitative approach was employed, and data were collected through a survey using questionnaires. The population of this study consisted of all 395 employees of PT PLN Nusa Daya UL Ketapang. The sample was determined using a probability sampling method with a simple random sampling technique, resulting in 199 respondents based on Slovin’s formula. Prior to data collection, the research instrument was tested on 30 respondents outside the sample to ensure its validity and reliability. The results of the testing indicated that all questionnaire items were valid and reliable, making them suitable for use in this study. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS 3 software. Model evaluation was performed through outer model and inner model assessments, as well as mediation testing using the Variance Accounted For (VAF) approach. The results of the study indicate that leadership and work climate have a positive and significant effect on employee performance. In addition, leadership and work climate also have a positive and significant effect on organizational commitment. Furthermore, organizational commitment has a positive and significant effect on employee performance and is able to mediate the relationship between leadership, work climate, and employee performance.